Regulation by Prices, Quantities, or Both: A Review of Instrument Choice. - Hepburn, C (2006)
Choosing appropriate policy instruments is an important part of successful regulation. Once objectives are agreed and suitable targets adopted, policy-makers can employ command-and-control regulation and/or economic instruments, and choose between fixing a price or a quantity. This paper examines the relative advantages of price, quantity, and hybrid instruments according to: their efficiency under uncertainty; the trade-off between credible commitment and flexibility; implementation; international considerations; and political economy. Various illustrations of the theory are provided, with two detailed applications to climate change and transport policy, specifically congestion and 'safety pricing'.